Analisis Pengurusan Dan Perawatan Terhadap Tahanan Pelaku Tindak Pidana Narkotika Di Rumah Tahanan Polda Bengkulu - Putra, Ayranda Eka; Amancik, Amancik; Jalili, Ismail (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
Police detainees are individuals suspected of committing criminal acts who are held in police detention centers. During their detention period, suspects are placed in the Bengkulu Regional Police Detention Center (Rutan Polda Bengkulu), under the responsibility of investigators and detention officers to ensure proper legal procedures. This study aims to analyze whether the management and care of narcotics offenders in the Bengkulu Police Detention Center are in accordance with existing legal provisions, and to identify the factors that hinder such management and care. The research used four techniques: (1) Population and Sample Determination, which included all police officers of the Directorate of Detention and Evidence (Dit Tahti) at the Bengkulu Regional Police and all narcotics detainees; (2) Data Collection using primary and secondary data; (3) Data Processing through coding and editing; and (4) Data Analysis using a qualitative descriptive method with a normative-empirical approach. The findings show: (1) Management and care of narcotics detainees at the Bengkulu Police Detention Center are in accordance with applicable laws and regulations, including: Perkap No. 4 of 2005, Perkap No. 4 of 2015, Law No. 12 of 1995, Law No. 39 of 1999, Law No. 35 of 2009, Law No. 5 of 1997, Law No. 2 of 2002, and Presidential Regulation No. 58 of 1999. (2) Factors hindering effective detainee management and care include: the classification of narcotics detainees as special detainees, ineffective service procedures, overcrowded cells, lack of officer knowledge on detainee care, limited medical personnel, short detention periods, and minimal involvement from related government agencies.